The Use Of Deixis In The Short Story Nasihat-Nasihat By A.A. Navis - Achmad Mudani; Ach. sayfullah (Penerbit Hellow Pustaka, 2024)
This study analyzes the use of deixis in the short story Nasihat-nasihat by A.A. Navis. Deixis is a linguistic element that refers to words or phrases whose meanings depend on context, such as person, place, and time. The purpose of this study is to identify the types of deixis used in the short story, including person, place, time, discourse, and social deixis. The research method used is descriptive qualitative with content analysis techniques on the short story text. The results of the study indicate that person deixis is most dominantly used in this short story, especially in the dialogue between characters who play a role in conveying the moral message of the story. In addition, time and place deixis are used to clarify the setting of the story, while social deixis reflects the hierarchical social relationship between characters. This study concludes that the use of deixis in the short story Nasihat-nasihat not only functions as a referential marker, but also contributes to the development of themes and characters.